Three new species of arbuscular mycorrhizal fungi (Glomeromycota) and Acaulospora gedanensis revised - Piotr Niezgoda; Janusz Błaszkowski; Tomasz Błaszkowski; Anna Stanisławczyk; Szymon Zubek; Paweł Milczarski; Ryszard Malinowski; Edward Meller; Monika Malicka; Bruno Tomio Goto; Sylwia Uszok; Leonardo Casieri; et al. (Frontiers in Microbiology, 2024)
Studies of the morphology and the 45S nuc rDNA phylogeny of three potentially undescribed arbuscular mycorrhizal fungi (phylum Glomeromycota) grown in cultures showed that one of these fungi is a new species of the genus Diversispora in the family Diversisporaceae; the other two fungi are new Scutellospora species in Scutellosporaceae. Diversispora vistulana sp. nov. came from maritime sand dunes of the Vistula Spit in northern Poland, and S. graeca sp. nov. and S. intraundulata sp. nov. originally inhabited the Mediterranean dunes of the Peloponnese Peninsula, Greece. In addition, the morphological description of spores of Acaulospora gedanensis, originally described in 1988, was emended based on newly found specimens, and the so far unknown phylogeny of this species was determined. The phylogenetic analyses of 45S sequences placed this species among Acaulospora species with atypical phenotypic and histochemical features of components of the two inner germinal walls.